Strategic management in improving employee performance pt. Riau agrindo agung - Yuni Permata Sari; Harius Eko Saputra; Tuti Handayani; Yanuar Rikardo (Penerbit Jurnal Indonesia, 2023)
This study aims to determine the management strategy in improving employee Performance at PT. Riau Agrindo Agung. This study used descriptive qualitative method. The data collection used is interview techniques, and documentation. Based on the results of the study it is known that: (1) Strengths owned by PT. Riau Agrindo Agung in improving employee performance are: (a) complete work facilities, (b) good quality of integrated human resources, (c) fully owned company legality. (2) Weaknesses owned by PT. Riau Agrindo Agung in improving employee performance are: (a) the location to access the plantation which is far from residential areas, (b) the distance between the divisional or abdeling offices to the estate office which is quite far. (3) Opportunities owned by PT. Riau Agrindo Agung in improving employee performance is: (a) Giving appreciation in the form of awards or certificates for employees, (b) Opening jobs for the community around the plantation location. (4) Threats owned by PT. Riau Agrindo Agung in Improving Employee Performance are: (a) miss communication between employees in terms of giving premi (overtime orders). (b) the theft rate of FFB is high so that the company is threatened with low production.